2001
DOI: 10.1128/jcm.39.2.514-518.2001
|View full text |Cite
|
Sign up to set email alerts
|

Nosocomial Fungemia Due to Exophiala jeanselmei var. jeanselmei and a Rhinocladiella Species: Newly Described Causes of Bloodstream Infection

Abstract: Fungi have become increasingly important causes of nosocomial bloodstream infections. The major cause of nosocomial fungemia has been Candida spp, but increasingly molds and other yeasts have caused disease. Exophiala jeanselmei and members of the genus Rhinocladiella are dematiaceous moulds, which have been infrequently associated with systemic infection and have not been described as causes of fungemia. In this paper, the occurrence of 23 cases of fungemia due to these organisms over a 10-month period is rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
27
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(32 citation statements)
references
References 25 publications
4
27
0
1
Order By: Relevance
“…Epidemics caused by these species have not been observed, but repeated reports of pseudoepidemics due to contaminated fluids have been published (2,33,34). In the large set of strains analyzed for the present study, 12 of the 17 known invasive species were encountered, with the exception of E. castellanii, E. moniliae, E. nishimurae, E. salmonis, and E. pisciphila.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Epidemics caused by these species have not been observed, but repeated reports of pseudoepidemics due to contaminated fluids have been published (2,33,34). In the large set of strains analyzed for the present study, 12 of the 17 known invasive species were encountered, with the exception of E. castellanii, E. moniliae, E. nishimurae, E. salmonis, and E. pisciphila.…”
Section: Discussionmentioning
confidence: 84%
“…Most of these species have been reported from proven clinical cases, whereby slight, species-specific differences in preferred sites of infection were noted (15). Unfortunately, case reports continue to be published under obsolete concepts (33,34) and thus create confusion. The present study utilizes species circumscriptions pub- lished after the latest overview of clinically relevant Exophiala species, which dates back to the year 2000 (9).…”
Section: Discussionmentioning
confidence: 99%
“…The environmental strains clustering in this group mostly originated from low-nutrient or sugary substrates, such as honey or silicone, or were found on damp surfaces on inert material in saunas and swimming pools (Table 1). Nucci et al (30,31) reported a nosocomial outbreak of 19 cases of fungemia caused by E. jeanselmei and originating from contaminated hospital water. All of the strains were shown to be strictly identical.…”
Section: Discussionmentioning
confidence: 99%
“…An additional benefit is the minimal tissue loss with surgical removal of the lesions. 12 Complete surgical resection of localized lesions results in cure with no recurrence in the major- 3,8,11,13,14 Although the study conducted by Silveira and Nucci (2001) showed high minimum inhibitory concentration (MIC) values for dematiaceous fungi in general with fluconazole 15 , in the present case report the use of fluconazole preceding surgery led to a reduction in the size of the lesion and principally in the inflammatory process, improving local conditions during surgery and facilitating surgical removal of the entire lesion.…”
Section: Discussionmentioning
confidence: 85%